MANAGEMENT OF 35 % HYDROGEN PEROXIDE EXPOSURE TO NAKED EYES: A CASE REPORT AND REVIEW - SREERAM S R,; PRABHATH SINGH,; PREETHEE THOMAS,; K N UNNI,; S THARANI, (International Journal of Pharma and Bio Sciences, 2015)
Exposure of strong acids to eyes is a rare uneventful situation. This case reports one such case where accidental exposure of dental bleaching agent which contain 35 percent of hydrogen peroxide to patients naked eyes in a dental office which was successfully managed without any corneal damage